2022
DOI: 10.1111/jora.12739
|View full text |Cite
|
Sign up to set email alerts
|

Black Lives and Black Research Matter: How our Collective Emotions Continue to Drive a Movement

Abstract: The author discusses (1) how the collective emotional experience of the Black community has propelled two parallel movements, Black Lives Matter and Black Research Matters, (2) the state of developmental science as it pertains to Black youth, and (3) suggestions for future research to integrate across fields and to evolve beyond Black pain to incorporate Black joy. The author suggests that the palpable anger collectively felt and expressed as a community has propelled a host of social‐political actions to dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…An integrative multi-disciplinary approach to collective phenomena is likely to elucidate their universal bases, while clarifying the existence of cultural specificities. Finally, putting empirical predictions to the test is crucial if we aim to understand the role of collective emotion in group behaviours related to a broad range of societal topics, such as social movements (Dunbar, 2022), group conflicts (Bar-Tal et al, 2007), responses to terrorist attacks (Garcia & Rimé, 2019), pandemics (Metzler et al, 2023) and climate change (Fritsche & Masson, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrative multi-disciplinary approach to collective phenomena is likely to elucidate their universal bases, while clarifying the existence of cultural specificities. Finally, putting empirical predictions to the test is crucial if we aim to understand the role of collective emotion in group behaviours related to a broad range of societal topics, such as social movements (Dunbar, 2022), group conflicts (Bar-Tal et al, 2007), responses to terrorist attacks (Garcia & Rimé, 2019), pandemics (Metzler et al, 2023) and climate change (Fritsche & Masson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies could contrast dyads with groups of three and up to, e.g., six participants. Indeed, previous research indicated that human groups spontaneously split into subgroups of about three to four people in the context of conversations (Dunbar et al, 1995) and laughter (Dezecache & Dunbar, 2012). Based on cases studies of collective emotions (e.g., Sullivan & Day, 2019;Sullivan, 2018), future experimental research could also investigate the influence of other group features such as its structure (e.g., reciprocity and strength of connections, presence of an out-group) and the balance between homogeneity and heterogeneity across individuals (e.g., diversity in the motives of participants, leaderfollower relationships).…”
Section: Group Sizementioning
confidence: 99%
“…Adolescents are more than the oppressions they face; they resist, have dreams, and have many other rich lived experiences across many developmental contexts. Indeed, many papers in the special series honored the humanity of Black youth and other youth of color by moving beyond a singular focus on the impacts of racism and oppression to documenting the complexity of whole personhood and celebrating strengths (Carey et al, 2022;Carter & Flewellen, 2022;Dunbar, 2022;López Hernández, 2022;Mathews et al, 2022;May et al, 2022;Rogers & Butler-Barnes, 2022). Additionally, anti-racist research can move beyond damage-centered research by conceptualizing research in ways that are action-oriented and community-informed to "engage diverse publics" (Eaton et al, 2021(Eaton et al, , p. 1214.…”
Section: Concep T Ua Lizi Ng R Acism As Syste M Icmentioning
confidence: 99%